Optimizing vehicle routing and scheduling under time constraints - Bala Karlo; Bandecchi Michele; Brcanov Dejan; Gvozdenović Nebojša (Anali Ekonomskog fakulteta u Subotici)
The Vehicle Routing Problem is essential in logistics for optimizing customer routes, especially in timesensitive variants. This paper presents a two-stage algorithm for Vehicle Routing Problem with Time Windows. It effectively minimizes the number of vehicles, with transportation costs resulting just 0,38% above the best solution found on Solomon test instances. The approach limits search time to about 10 minutes, effectively balancing complexity and solution quality.